2006
DOI: 10.1007/s11010-006-9270-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of antioxidant systems, lipid peroxidation, and nitric oxide in postmenopausal osteoporosis

Abstract: In this study we assessed activities of antioxidant enzymes, lipid peroxidation end-products, and nitric oxide (NO) levels in women with postmenopausal osteoporosis (PMO). Relationship between oxidative stress parameters and NO levels with bone mineral density (BMD) and clinical variables influencing bone mass and health related quality of life measures was also investigated in women with PMO. Postmenopausal women (n=87), aged 40-65, without previous diagnosis or treatment for osteoporosis and independent in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(146 citation statements)
references
References 36 publications
12
122
0
8
Order By: Relevance
“…Previously, VA has been reported to exhibit estrogenic activity, and hence we hypothesize that VA may favor the anti-osteoporotic property by acting as estrogen analog (Xiao et al, 2014). Since, estrogen plays a critical role in maintaining bone mineralization and remodeling (turnover) process via regulating the balance between osteoclast and osteoblast (Ozgocmen et al, 2007). Hence, the present experiment was designed to evaluate the anti-osteoporotic property of VA in ovariectomy-induced rat model which mimic postmenopausal osteoporosis.…”
Section: Resultsmentioning
confidence: 98%
“…Previously, VA has been reported to exhibit estrogenic activity, and hence we hypothesize that VA may favor the anti-osteoporotic property by acting as estrogen analog (Xiao et al, 2014). Since, estrogen plays a critical role in maintaining bone mineralization and remodeling (turnover) process via regulating the balance between osteoclast and osteoblast (Ozgocmen et al, 2007). Hence, the present experiment was designed to evaluate the anti-osteoporotic property of VA in ovariectomy-induced rat model which mimic postmenopausal osteoporosis.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have revealed that SOD2 is significantly upregulated in circulating monocytes at the mRNA and protein level in vivo in Chinese patients with low versus high hip BMD levels (49). Women with postmenopausal osteoporosis have significantly higher plasma SOD enzyme activity levels than those in controls (50). This indicates that SOD2 is significant in the pathogenesis of osteoporosis, promoting osteoclast differentiation, formation and activity (51).…”
Section: Discussionmentioning
confidence: 98%
“…The impact of NO on bone metabolism is two-way directional, affecting not only the function of osteoclasts, but also the differentiation and proliferation of osteoblasts (Brennan et al, 2003;van't Hof et al, 2004). It has been found that NO is related with osteoporosis development in postmenopausal women (Ozgocmen et al, 2007;Rosselli et al, 1995). During menstrual cycle, blood NO metabolite concentrations correlate with estrogen levels, being higher in the follicular phase than in the secretory phase (Cicinelli et al, 1996).…”
Section: Introductionmentioning
confidence: 99%